2017
DOI: 10.3221/igf-esis.43.06
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength of corroded bolted connection

Abstract: This note summarizes some recent investigation results on the behavior of corroded steel bolted joints under uniaxial fatigue loading. Fatigue test specimens, were made up using S355 structural steel plates joined together with preloaded M12 bolts of class 10.9 with a geometry that corresponds to the Δσ = 112 MPa EC3 detail category. The accelerated corrosion process was accomplished using an electrolyte consisting of an aqueous 5% NaCl solution whereby the specimens were treated. In particular, during the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Zampieri [17] studied the fatigue strength of bolted connections, which indicates that corrosion can influence the fatigue life of the joint. Moreover, extended studies were done by Zampieri et al [18,19] that showed the degradation of the corroded bolted joint due to pitting corrosion. Besides, relevant studies suggested that the pitting flaw initiated by corrosion could be regarded as the source of fatigue cracking [14,16,20].…”
Section: Literature Reviewmentioning
confidence: 89%
“…Zampieri [17] studied the fatigue strength of bolted connections, which indicates that corrosion can influence the fatigue life of the joint. Moreover, extended studies were done by Zampieri et al [18,19] that showed the degradation of the corroded bolted joint due to pitting corrosion. Besides, relevant studies suggested that the pitting flaw initiated by corrosion could be regarded as the source of fatigue cracking [14,16,20].…”
Section: Literature Reviewmentioning
confidence: 89%
“…The Bayesian updating is considered to be one of the probabilistic methods for updating the existing probability distribution by reflecting the inspection data of the bridge [12]. Moreover, it can be expressed as Equation 3.…”
Section: General Bayesian Updatingmentioning
confidence: 99%
“…These days, the bridge deterioration model based on regression analysis is conducted to derive an efficient maintenance method for bridge management system in advanced countries, such as the USA, Japan, and Australia [1][2][3]. Domestic and foreign research trends related to bridge maintenance denote that they have focused on estimating the bridge performance changes with high accuracy through monitoring technologies based on unmanned inspection devices (sensors, drones, or robots) and by establishing an optimal maintenance decision making process system [4][5][6][7][8][9][10][11][12][13][14][15]. In addition, Bayesian deterioration model updating for maintenance cost estimation in steel box girder bridges has been proposed [16].…”
Section: Introductionmentioning
confidence: 99%
“…He observed that the failure was caused by the combination of a missing interior weld, a ductile tear, and fatigue cracking. Zampieri et al have investigated the influence of the corrosive phenomenon on the fatigue strength of a friction type joint made of high strength preloaded bolts [3]. They observed that the accelerated corrosion process applied to the specimens caused a not negligible reduction of the fatigue strength of joints.…”
Section: Introductionmentioning
confidence: 99%
“…Considering a behavior-damage coupling of the material, finite element numerical simulations were carried out on XC65 steel pipes with pitting in the axial direction. Depending on the size of the corrosion defect (length and width) [3].for a depth equal to 10% of the pipe wall thickness, the critical or dangerous area where the equivalent Von Mises stress is maximal is determined by the finite element code ANSYS [7]. The calculation of the crack initiation conditions in the critical area is obtained from the history of strain components taken as the output of the finite element calculation.…”
Section: Introductionmentioning
confidence: 99%